Financial restructuring of financial distressed firms / Norsyamira Ayub - Ayub, Norsyamira (2007)
Solving a corporate distress is very important for every company. There are wide variety of restructuring strategies for recovery that can be chosen by firms such as managerial, operational, assets and financial restructuring. Thus, this paper is focusing on the financial restructuring activities to see whether debt restructuring or equity restructuring is an appropriate tools to solve the financial distress. A sample of 81 distressed syariah compliant firms listed on the main board and the second board of Bursa Malaysia from the period of 2000 until 2002 is taken for this research. Logistic regression has been employed to asses whether the debt and equity restructuring contribute to recovery from financial distress. The expected result will be the distressed firm will usually restructure its debt position in order to solve the financial distress